Penetration efficieny of small size conical shaped charges in steel targets (Rudarsko-geološko-naftni zbornik, 2018)
This paper describes the research on testing of small size point focal shaped charges. They were manufactured from composite-B, Semtex and pressed RDX, and binary explosives, and emulsions. As the liner and the whole structure of the charges were identical the mild steel penetration test was a clear method for comparing and quantifying their performance. The target setup was also standardized with different steel discs. During testing I realized that it was a practical development tool, to find a proper mixture for binary explosives. Since most of the shaped charge literature related to their evaluation was rather detailed theoretical work, I wanted to have a simple, yet productive performance testing method that suited more to practical field works.